Transitioning insomnia patients from zolpidem to lemborexant: A multicenter, open-label study evaluating a next-dose transition approach to insomnia pharmacotherapy - Maha Ahmad; James Kelly; C. Brendan Montano; Dinesh Kumar; Carlos Perdomo; Manoj Malhotra; Jess Amchin; Margaret Moline (Sleep Medicine: X, 2024)
Objective: Few clinical studies have assessed real-world abrupt transitioning between insomnia medications. This study assessed strategies for directly transitioning patients from zolpidem tartrate (ZOL) immediate/extended release to the dual orexin receptor antagonist, lemborexant (LEM). Methods: This randomized, open-label, multicenter study (Study 312; E2006-A001-312) enrolled 53 adults age ≥18 years with insomnia disorder and ≥1-month history of intermittent (3–4 nights/week) or frequent (≥5 nights/week) ZOL use. Subjects recorded their ZOL use in a 3-week Pretreatment Phase, followed by a 2-week Treatment Phase (TRT; Titration) during which ZOL was discontinued. Intermittent ZOL users transitioned to LEM 5 mg (LEM5), Cohort 1, and frequent ZOL users were randomized 1:1 to LEM5, Cohort 2A, or LEM 10 mg (LEM10), Cohort 2B. One dose adjustment was permitted during the TRT. Subjects completing the TRT could continue LEM in the 12-week Extension Phase (EXT). The primary outcome was proportion of subjects who successfully transitioned and remained on LEM at the end of the TRT. Results: Most subjects (43 [81.1 %]) successfully transitioned to LEM (9 [90 %], 17 [81.0 %], and 17 [77.3 %] in Cohorts 1, 2A, and 2B, respectively). By the end of the EXT, 66.7 % in Cohort 1 and 60.0 % in Cohort 2A up-titrated to LEM10, whereas 41.2 % in Cohort 2B down-titrated to LEM5; 61.0 % were receiving LEM10 at study end. At the end of the TRT, more subjects taking LEM reported that it helped them return to sleep after waking, compared with those taking ZOL (71.7 % vs. 49.1 %). There were no important differences between treatments regarding how subjects reported feeling as they fell asleep. Most of the treatment-emergent adverse events with LEM were mild in severity. Conclusions: Most subjects transitioned successfully to LEM from ZOL (intermittent or frequent use). LEM was well tolerated.